Cyanide-free electrolyte, preparation method thereof and hard gold prepared from cyanide-free electrolyte

By adopting cyanocarcium electrolyte in the golden power casting, the use of sodium sulfuric acid sodium, diharamine, organic salt and other ingredients to solve the toxicity and environmental pollution of traditional cyanide electrolytes, and improved the hardness and products of gold products Quality realizes the green and sustainable power casting process.

CN119372722APending Publication Date: 2025-01-28东莞市利达黄金精炼有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411501849.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing gold products have low hardness and poor wear resistance, and traditional cyanide electrolytes have toxicity and environmental pollution problems, which limits the innovation and development of gold products.

Method used

A cyanoma -free electrolyte, which contains sodium sodium sodium sulfate, ethomine, organic rigida, coatings, pH buffer, and sodium -free sodium sodium sodium. Through the combination of these ingredients With the current efficiency of cathode, refine the grains of the casting layer, and improve the hardness and product quality of gold products.

Benefits of technology

The good stability of cyanoma -free solution and the efficiency of high cathode current, the hard gold made of high hardness, bright surface, and the phenomenon of foaming, deformation, and crushing after the fire burned, which improved the performance of gold products, which improved the performance of gold products. And reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102813170000081
    Figure BDA0005102813170000081
  • Figure BDA0005102813170000091
    Figure BDA0005102813170000091
Patent Text Reader

Abstract

The invention relates to the field of gold products, and particularly discloses a cyanide-free electrolyte, a preparation method of the cyanide-free electrolyte and hard gold prepared from the cyanide-free electrolyte. The cyanide-free electrolyte contains sodium gold sulfite, ethylenediamine, organic phosphine salt, a coordination agent, a pH buffer agent and anhydrous sodium sulfite, and the coordination agent is 3-mercaptopropionic acid or mercaptosuccinic acid. The cyanide-free electrolyte has good stability, the current efficiency of a cathode in the electroforming process can be high, and a finally obtained gold casting layer is small in grain size and high in density and has good coating color, uniformity and brightness; the hard gold prepared through electroforming of the cyanide-free electrolyte has high hardness and a bright surface, and the surface is not prone to blistering, deformation, smashing and the like after burning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of gold products, and more specifically, to a cyanide-free electrolyte and a preparation method thereof, and hard gold prepared from the cyanide-free electrolyte. Background Art

[0002] With the improvement of people's living standards, gold products are becoming more and more popular among consumers. However, high-purity pure gold and 999 gold have shortcomings such as low hardness, poor wear resistance and easy plastic deformation, which greatly restricts the innovation and development of gold product styles. For this reason, people increase the thickness or add filler materials in the traditional processing process to improve the strength of gold products. The emergence of electroforming technology around 2005 enables the gold product processing industry to produce gold products with higher strength than ordinary gold processing technology. At present, gold products made by electroforming technology have accounted for about 30% of the total sales of gold products, becoming a key factor in the healthy development of the gold product industry.

[0003] The electroforming process is a process that uses the principle of an electrolytic cell to deposit a gold layer on the surface of a cathode core coated with a conductive film, and then removes the core to achieve a precise replication of the cathode core. The process mainly includes four parts: power supply, electrolyte, cathode and anode, among which the electrolyte is mainly a cyanide-containing electrolyte. For gold electroforming, the cyanide system has a high stability. For a long time, the gold electroforming process has been making certain improvements around the cyanidation process. However, due to the highly toxic nature of cyanide, it will not only harm the health of the manufacturer during the production of gold products, but also cause serious pollution to the environment. At the same time, cyanide also has many hidden dangers in the transportation and storage of cyanide. Therefore, in order to achieve environmental protection and green and sustainable development of the electroforming process, the development of cyanide-free electrolyte has great social value and economic benefits.

[0004] Since the 1960s, the cyanide-free electrolytes with relatively mature theoretical foundations mainly include sulfite system, thiosulfate system, citrate system and hydantoin derivative complexing agent system, among which the sulfite system has been the most widely studied. Sulfite electrolyte has good dispersibility and deep plating ability, as well as high current efficiency, fast deposition speed, bright and uniform coating surface color, etc. However, sulfite electrolyte has poor stability and is very easy to precipitate gold during the electroforming process, thus affecting the stability of the electroforming process and the performance of gold products. The hardness of the gold products obtained is low, and the surface is prone to blistering, deformation, and crushing after being burned. This makes most hard gold products on the market have the disadvantages of being easily damaged and unable to be repaired after damage. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a cyanide-free electrolyte and a preparation method thereof, and hard gold prepared from the cyanide-free electrolyte.

[0006] In the first aspect, the present application provides a cyanide-free electrolyte, which adopts the following technical solution: A cyanide-free electrolyte contains sodium gold sulfite, ethylenediamine, an organic phosphonic salt, a complexing agent, a pH buffer and anhydrous sodium sulfite, wherein the complexing agent is 3-mercaptopropionic acid or mercaptosuccinic acid.

[0007] By adopting the above technical solution, the present invention adopts sodium gold sulfite as the main salt, and Au(SO3)2 3- It exists in the form of complex ions, providing gold elements for the electroforming process. At the same time, ethylenediamine and anhydrous sodium sulfite are used as stabilizers and auxiliary complexing agents to stabilize the electrolyte and inhibit Au(SO3)2 3- The role of complex ion dissociation. The cyanide-free electrolyte of the present application also contains an organic phosphonate, which is potassium hydroxyethylidene diphosphonate and / or sodium hydroxyethylidene diphosphonate. The presence of the organic phosphonate can significantly improve the current efficiency of the cathode during the electroforming process, thereby depositing more metallic gold in the same time and improving production efficiency; and it can form a stable complex with gold ions in the electrolyte, and together with ethylenediamine and anhydrous sodium sulfite, it plays a role in stabilizing the electrolyte and refining the grains, thereby obtaining a more dense and smooth cast gold layer, improving the hardness and product quality of the gold products finally obtained, and making the surface of the gold products less prone to blistering, deformation, crushing, etc. after being burned. The pH buffer of the present application can stabilize the pH value of the electrolyte within a certain range, thereby improving the stability of the complex in the electrolyte, reducing the possibility of decomposition of the complex due to pH fluctuations, and improving the quality of the gold products finally obtained.

[0008] In addition, the present application also adds 3-mercaptopropionic acid or mercaptosuccinic acid into the electrolyte as a ligand to react with gold ions, which can be coordinated with diethylamine, anhydrous sodium sulfite and organic phosphonic acid, greatly improving the stability of the electrolyte and refining the grains, thereby further increasing the density and brightness of the cast gold layer, thereby improving the hardness and product quality of the final gold product.

[0009] Preferably, the complexing agent is mercaptosuccinic acid.

[0010] By adopting the above technical scheme, compared with 3-mercaptopropionic acid, the present application further adopts mercaptosuccinic acid as a ligand, which can make the grains of the cast gold layer mostly continuous and tight spherical structures, thereby further improving the density of the cast gold layer, and then improving the hardness and product quality of the final gold product.

[0011] Optionally, the content of sodium gold sulfite in the cyanide-free electrolyte (in terms of gold) is 0.5-4 g / L, the molar ratio of ethylenediamine to gold is (3-15):1, the content of organic phosphine salt is 3-4 mL / L, the content of mercaptosuccinic acid is 3.375-16.875 g / L, the pH buffer is 10-50 g / L, and the anhydrous sodium sulfite is 5-33 g / L.

[0012] Preferably, the content of sodium gold sulfite (in terms of gold) in the cyanide-free electrolyte is 1-4 g / L.

[0013] By adopting the above technical solution, the present application further controls the content of sodium gold sulfite in the cyanide-free electrolyte, which can further improve the current efficiency of the cathode during the electroforming process, refine the grain size of the cast gold layer, improve the surface hardness of the hard gold, and make the prepared cast gold layer have good coating color, brightness, uniformity and density.

[0014] Preferably, the molar ratio of ethylenediamine to gold in the cyanide-free electrolyte is (6-10):1.

[0015] By adopting the above technical solution, the present application further optimizes the amount of ethylenediamine added, so that the cathode has a higher current efficiency during the electroforming process, and the obtained cast gold layer has good coating color, brightness, uniformity and density, and the electrolyte is not prone to turbidity.

[0016] Preferably, the content of mercaptosuccinic acid in the cyanide-free electrolyte is 6.750-13.500 g / L.

[0017] By adopting the above technical solution, the present application further optimizes the addition amount of mercaptosuccinic acid, promotes the preferential growth of the cast gold layer along the Au (111) crystal plane, improves the density and stability of the cast gold layer, thereby improving the surface hardness of the final gold product, and at the same time enables the cathode to maintain a high current efficiency during the electroforming process, thereby improving production efficiency.

[0018] Preferably, the content of anhydrous sodium sulfite in the cyanide-free electrolyte is 13-23 g / L.

[0019] By adopting the above technical solution, the present application further optimizes the addition amount of anhydrous sodium sulfite, so that the cathode has a higher current efficiency during the electroforming process, and the obtained cast gold layer has good coating color, brightness, uniformity and density.

[0020] Preferably, the pH buffer is a citric acid-disodium hydrogen phosphate system.

[0021] By adopting the above technical scheme, the present application further selects a citric acid-disodium hydrogen phosphate system as a pH buffer for the cyanide-free electrolyte, which can further improve the stability of the electrolyte, refine the grain size of the cast gold layer, enhance the density of the cast gold layer, and improve the surface hardness of the cast gold layer.

[0022] In a second aspect, the present application provides a method for preparing a cyanide-free electrolyte, which adopts the following technical solution: A method for preparing a cyanide-free electrolyte comprises the following steps: S1. Preparation of sodium gold sulfite Dissolving the gold flakes in aqua regia at a temperature of 70-80°C and concentrating the solution by evaporation to one sixth of the original volume to obtain gold trichloride, then diluting the gold trichloride with water, adding ammonia water thereto and stirring the solution until a precipitate is formed to obtain gold fulminate, then mixing the gold fulminate with anhydrous sodium sulfite solution at a temperature of 40-60°C until the gold fulminate is completely dissolved, and then cooling to obtain sodium gold sulfite; S2. Preparation of cyanide-free electrolyte The gold sodium sulfite, ethylenediamine, organic phosphine salt, complexing agent, pH buffer and anhydrous sodium sulfite prepared in step S1 are added into water and mixed evenly, and the pH value of the system is adjusted to 8-9 to obtain a cyanide-free electrolyte.

[0023] In a third aspect, the present application provides hard gold obtained by electroforming with a cyanide-free electrolyte prepared by the above-mentioned preparation method.

[0024] Through the above technical scheme, the gold products electroformed by the present application using the above cyanide-free electrolyte have high hardness and a bright surface, and the surface is not prone to blistering, deformation, crushing, etc. after being burned.

[0025] In summary, this application has the following beneficial technical effects: 1. The cyanide-free electrolyte of the present application has good stability and can make the current efficiency of the cathode higher during the electroforming process. The final cast gold layer has a smaller grain size, higher density, and good coating color, uniformity and brightness. 2. The hard gold electroformed by the cyanide-free electrolyte of the present application has higher hardness and a bright surface. After being burned, the surface is not prone to blistering, deformation, crushing, etc. DETAILED DESCRIPTION

[0026] The present application is further described in detail below in conjunction with embodiments.

[0027] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, including: Gold flakes, purity 99.99%, thickness 1mm; Aqua regia, concentrated hydrochloric acid and concentrated nitric acid are mixed in a volume ratio of 3:1; Potassium hydroxyethylidene diphosphonate, CAS number is 67953-76-8; Sodium hydroxyethylidene diphosphonate, CAS No. 29329-71-3, abbreviated as HEDP·NA, was purchased from Hubei Langbowan Biopharmaceutical Co., Ltd.; 3-Mercaptopropionic acid, CAS number is 107-96-0; Mercaptosuccinic acid, CAS number is 70-49-5.

[0028] Example 1 A method for preparing a cyanide-free electrolyte comprises the following steps: S1. Preparation of sodium gold sulfite Cut the gold flakes into thin strips, then add the prepared aqua regia, add 12 mL of aqua regia for every 1 gram of the gold flakes, then heat it to 70°C to completely dissolve the gold flakes in the aqua regia, and evaporate and concentrate the solution to one sixth of the original volume at the same temperature to obtain gold trichloride, then add water with a volume 5 times the volume of the solution to dilute the gold trichloride, then add ammonia water thereto and stir the solution until a precipitate is generated to obtain gold fulminate, then add anhydrous sodium sulfite solution to the gold fulminate, the amount of anhydrous sodium sulfite used is 4 times the weight of the gold flakes, and heat it to 40°C to completely dissolve the gold fulminate, and then cool it to obtain sodium gold sulfite; S2. Preparation of cyanide-free electrolyte The sodium gold sulfite, ethylenediamine, potassium hydroxyethylidene diphosphonate, mercaptosuccinic acid, pH buffer and anhydrous sodium sulfite prepared in step S1 are mixed, and a certain volume of water is added thereto and stirred evenly, so that the content of sodium gold sulfite in the solution (in terms of gold) is 0.5 g / L, the molar ratio of ethylenediamine to gold flakes is 15:1, the content of potassium hydroxyethylidene diphosphonate is 3 mL / L, the content of mercaptosuccinic acid is 16.875 g / L, the content of pH buffer is 10 g / L, the content of anhydrous sodium sulfite is 33 g / L, and the pH value is adjusted to 8 according to the actual pH value of the system to obtain a cyanide-free electrolyte, wherein the pH buffer is a citric acid-disodium hydrogen phosphate system, and the volume ratio of citric acid to disodium hydrogen phosphate is 1:4.7.

[0029] Example 2 A method for preparing a cyanide-free electrolyte comprises the following steps: S1. Preparation of sodium gold sulfite Cut the gold flakes into thin strips, then add the prepared aqua regia, add 13 mL of aqua regia for every 1 gram of the gold flakes, then heat it to 80°C to completely dissolve the gold flakes in the aqua regia, and evaporate and concentrate the solution to one sixth of the original volume at the same temperature to obtain gold trichloride, then add water with a volume 5 times the volume of the solution to dilute the gold trichloride, then add ammonia water thereto and stir the solution until a precipitate is generated to obtain gold fulminate, then add anhydrous sodium sulfite solution to the gold fulminate, the amount of anhydrous sodium sulfite used is 4 times the weight of the gold flakes, and heat it to 60°C to completely dissolve the gold fulminate, and then cool it to obtain sodium gold sulfite; S2. Preparation of cyanide-free electrolyte The sodium gold sulfite, ethylenediamine, potassium hydroxyethylidene diphosphonate, mercaptosuccinic acid, pH buffer and anhydrous sodium sulfite prepared in step S1 are mixed, and a certain volume of water is added thereto and stirred evenly, so that the content of sodium gold sulfite in the solution (in terms of gold) is 4 g / L, the molar ratio of ethylenediamine to gold flakes is 3:1, the content of potassium hydroxyethylidene diphosphonate is 4 mL / L, the content of mercaptosuccinic acid is 3.375 g / L, the content of pH buffer is 50 g / L, the content of anhydrous sodium sulfite is 5 g / L, and the pH value is adjusted to 9 according to the actual pH of the system to obtain a cyanide-free electrolyte, wherein the pH buffer is a citric acid-disodium hydrogen phosphate system, and the volume ratio of citric acid to disodium hydrogen phosphate is 1:4.7.

[0030] Example 3 A method for preparing a cyanide-free electrolyte, which is different from Example 2 in that the mercaptosuccinic acid in step S2 is replaced by 3-mercaptopropionic acid, and the rest is the same as Example 2.

[0031] Example 4 A method for preparing a cyanide-free electrolyte, which is different from that of Example 2 in that: in step S2, the content of sodium gold sulfite in the solution (in terms of gold) is 0.5 g / L, and the rest is the same as that of Example 2.

[0032] Example 5 A method for preparing a cyanide-free electrolyte, which is different from that of Example 2 in that: in step S2, the content of sodium gold sulfite in the solution (in terms of gold) is 1 g / L, and the rest is the same as that of Example 2.

[0033] Example 6 A method for preparing a cyanide-free electrolyte, which is different from that of Example 2 in that: in step S2, the content of sodium gold sulfite in the solution (in terms of gold) is 3 g / L, and the rest is the same as that of Example 2.

[0034] Example 7 A method for preparing a cyanide-free electrolyte is different from that of Example 2 in that: in step S2, the molar ratio of ethylenediamine to gold in the solution is 6:1, and the rest is the same as that of Example 2.

[0035] Example 8 A method for preparing a cyanide-free electrolyte is different from that of Example 2 in that: in step S2, the molar ratio of ethylenediamine to gold in the solution is 10:1, and the rest is the same as that of Example 2.

[0036] Example 9 A method for preparing a cyanide-free electrolyte is different from that of Example 2 in that: in step S2, the molar ratio of ethylenediamine to gold in the solution is 15:1, and the rest is the same as that of Example 2.

[0037] Example 10 A method for preparing a cyanide-free electrolyte, which is different from Example 2 in that: in step S2, the content of mercaptosuccinic acid in the solution is 6.750 g / L, and the rest is the same as Example 2.

[0038] Embodiment 11 A method for preparing a cyanide-free electrolyte, which is different from Example 2 in that: in step S2, the content of mercaptosuccinic acid in the solution is 13.500 g / L, and the rest is the same as Example 2.

[0039] Example 12 A method for preparing a cyanide-free electrolyte, which is different from Example 2 in that: in step S2, the content of mercaptosuccinic acid in the solution is 16.875 g / L, and the rest is the same as Example 2.

[0040] Example 13 A method for preparing a cyanide-free electrolyte is different from that of Example 2 in that: in step S2, the content of anhydrous sodium sulfite in the solution is 13 g / L, and the rest is the same as that of Example 2.

[0041] Embodiment 14 A method for preparing a cyanide-free electrolyte is different from that of Example 2 in that: in step S2, the content of anhydrous sodium sulfite in the solution is 23 g / L, and the rest is the same as that of Example 2.

[0042] Embodiment 15 A method for preparing a cyanide-free electrolyte, which is different from that of Example 2 in that: in step S2, the content of anhydrous sodium sulfite in the solution is 33 g / L, and the rest is the same as that of Example 2.

[0043] Example 16 A method for preparing a cyanide-free electrolyte, which is different from that of Example 2 in that: in step S2, the pH buffer is a disodium hydrogen phosphate-sodium dihydrogen phosphate system, wherein the volume ratio of disodium hydrogen phosphate to sodium dihydrogen phosphate is 1:2.5, and the rest is the same as that of Example 2.

[0044] Embodiment 17 A method for preparing a cyanide-free electrolyte, which is different from that of Example 2 in that: in step S2, the pH buffer is an acetic acid-sodium acetate system, wherein the volume ratio of acetic acid to sodium acetate is 1:1.2, and the rest is the same as that of Example 2.

[0045] Comparative Example 1 The difference from Example 2 is that in step S2, mercaptosuccinic acid is not added, and the rest is the same as Example 2.

[0046] Comparative Example 2 The difference from Example 2 is that in step S2, mercaptosuccinic acid is replaced by 1-mercaptomethylcyclopropylacetic acid, and the rest is the same as Example 2.

[0047] Comparative Example 3 The difference from Example 2 is that in step S2, mercaptosuccinic acid is replaced by 2-amino-3-mercaptopropionic acid, and the rest is the same as Example 2.

[0048] Performance Testing 1. The stability and cathode current efficiency of the cyanide-free electrolytes prepared in the above embodiments and comparative examples were tested. The specific method was as follows: a copper sulfate electrolyte was prepared, which consisted of copper sulfate, sulfuric acid, ethanol and water, wherein the content of copper sulfate was 125 g / L, the content of sulfuric acid was 25 mL / L, and the content of ethanol was 50 mL / L. The copper sulfate electrolyte (1000 mL) and the cyanide-free electrolytes prepared in the above embodiments and comparative examples were placed in electrolytic cell a (size of 120 mm×120 mm×100 mm) and electrolytic cell b (size of 120 mm×120 mm×100 mm), respectively. A phosphor copper sheet (mixed and uniformly pressed by 99.94 wt% copper and 0.06 wt% phosphorus, with a density of 8.89 g / cm 3, with a size of 80mm×60mm×3mm) was placed in electrolytic cell a as an anode (referred to as anode a), a rhombus-shaped iridium-titanium composite material (composed of a metal titanium core layer and a metal iridium layer attached to the surface of the metal titanium core layer, with an average thickness of the metal iridium layer of 3μm, a side length of the rhombus in the rhombus-shaped iridium-titanium composite material of 10mm, and an acute angle between the sides of 60°) was placed in electrolytic cell b as an anode (referred to as anode b), and cathode test piece a (made of pure copper sheet, with a size of 25mm×25mm×0.3mm) and cathode test piece b (made of pure copper sheet, with a size of 25mm×25mm ×0.3mm) and then rinsed and weighed, then the cathode test piece a was placed in the electrolytic cell a, and the cathode test piece b was placed in the electrolytic cell b, then the anode a was connected to the positive electrode of the power supply through a wire, the cathode test piece a was connected to the anode b through a wire, and the cathode test piece b was connected to the negative electrode of the power supply through a wire, and then powered on, and electroformed for 10 minutes at a constant current of 0.03A, wherein the operating temperature of the electrolytic cell a was 25°C, and the operating temperature of the electrolytic cell b was 60°C. After the electroforming was completed, the cathode test piece a and the cathode test piece b were taken out, washed, dried and weighed, and the cathode current efficiency was calculated according to the following formula: η=0.165×ΔMa / ΔMb×100%(η: cathode current efficiency, ΔMa: increased weight of cathode test piece a, ΔMb: increased weight of cathode test piece b). A cathode current efficiency of 90% or more indicates that the cyanide-free electrolyte has high stability, while a cathode current efficiency of 85% or less indicates that the cyanide-free electrolyte has low stability. The specific test results are shown in Table 1.

[0049] Table 1 Cyanide-free electrolyte stability results project Cathode current efficiency (%) stability Example 1 95.8 high Example 2 94.6 high Example 3 93.4 high Example 4 92.7 high Example 5 94.2 high Example 6 93.8 high Example 7 96.3 high Example 8 95.6 high Example 9 97.2 high Example 10 94.1 high Embodiment 11 92.6 high Example 12 92.0 high Example 13 95.3 high Embodiment 14 94.9 high Embodiment 15 94.4 high Example 16 93.8 high Embodiment 17 94.1 high Comparative Example 1 82.3 Low Comparative Example 2 85.9 Lower Comparative Example 3 83.1 Low 1. The cyanide-free electrolyte prepared in the above embodiment and comparative example was used to carry out an electroforming process to prepare hard gold with a cast gold layer thickness of 170 μm. The electroforming process is a commonly used electroforming process in the art. The parameters of the electroforming process used in each group are exactly the same. Then, the surface grain size, hardness, brightness and uniformity of the hard gold were tested. The hard gold was burned with a fire gun at a temperature of 800-1000° C. to observe whether there were blistering, deformation, crushing and other phenomena on its surface. The test results are shown in Table 2; wherein, the grain size was measured by X-ray diffractometer (XRD); the hardness was measured by micro Vickers hardness tester to measure the Vickers hardness value of the sample, the test force was 1.98 N, and the contact time between the diamond and the sample was 15 s; the brightness and uniformity were visually inspected.

[0050] Table 2 Hard gold test results Data Analysis: It can be seen from Table 1 and Table 2 that the cathode current efficiency of the cyanide-free electrolyte prepared in Examples 1-2 of the present application is 94.6-95.8%, which indicates that the cyanide-free electrolyte prepared in Examples 1-2 has high stability, and the surface grain size of the hard gold electroformed by using the cyanide-free electrolyte is 42.1-43.2nm, the hardness is 147-151HV, the surface density is high, and the surface is bright and uniform, and no blistering occurs after burning.

[0051] The cathode current efficiency of the cyanide-free electrolyte prepared in Example 3 is lower than that in Example 2, and the surface grain size of the hard gold electroformed by the cyanide-free electrolyte prepared in Example 3 is larger than that in Example 2, and the hardness is lower than that in Example 2, which indicates that compared with 3-mercaptopropionic acid, the use of mercaptosuccinic acid as a ligand can further improve the cathode current efficiency, increase the stability of the cyanide-free electrolyte, refine the grain size of the cast gold layer, and improve the surface hardness of the hard gold.

[0052] The difference between Example 4-6 and Example 2 is that the content of sodium gold sulfite in the cyanide-free electrolyte (in terms of gold) is different. It can be seen from Table 1 and Table 2 that the cathode current efficiency of Example 4 is lower than that of Example 2 and Examples 5-6, and the particle size of the hard gold electroformed by the cyanide-free electrolyte obtained in Example 4 is larger than that of Examples 2 and Examples 5-6, and the surface hardness is lower than that of Examples 2 and Examples 5-6. The experimental data show that when the addition amount of sodium gold sulfite is too low, it will affect the production efficiency of the electroforming process, reduce the stability of the electrolyte, and affect the quality of the gold products finally obtained. In addition, it was found during the experiment that if the addition amount of sodium gold sulfite is too large, it will seriously affect the color of the gold products finally obtained.

[0053] The difference between Example 7-9 and Example 2 is that the amount of ethylenediamine added to the cyanide-free electrolyte is different. It can be seen from Table 1 and Table 2 that the cathode current efficiency of Example 7-9 is higher than that of Example 2. The particle size of the hard gold electroformed by the cyanide-free electrolyte prepared in Example 7-9 is smaller than that of Example 2, and the surface hardness is greater than that of Example 2. The experimental data show that when the amount of ethylenediamine added in Example 7-9 is further increased, the cathode current efficiency can be further improved, the stability of the cyanide-free electrolyte is increased, the grain size of the cast gold layer is refined, and the surface hardness of the hard gold is improved. However, it was found during the experiment that Example 9 has the problem of turbidity of the cyanide-free electrolyte, which indicates that if the amount of ethylenediamine added is too large, it will affect the clarity of the cyanide-free electrolyte, thereby affecting its stability.

[0054] The difference between Examples 10-12 and Example 2 is that the amount of mercaptosuccinic acid added is different. It can be seen from Tables 1 and 2 that with the increase in the amount of mercaptosuccinic acid added, the cathode current efficiency of the cyanide-free electrolyte gradually decreases, the particle size of the hard gold obtained by electroforming increases, but the surface hardness of the hard gold gradually increases. Through XRD analysis of the crystal structure, it is found that the increase in the amount of mercaptosuccinic acid added promotes the preferential growth of the cast gold layer along the Au (111) crystal plane, and the peak intensity of the Au (111) crystal plane gradually increases, thereby improving the density and stability of the surface of the cast gold layer, and then improving the surface hardness of the hard gold.

[0055] The difference between Example 13-15 and Example 2 is that the amount of anhydrous sodium sulfite added is different. It can be seen from Table 1 and Table 2 that the cathode current efficiency of the cyanide-free electrolyte prepared in Example 13-14 is higher than that in Example 2, and the particle size of the hard gold electroformed by the cyanide-free electrolyte prepared in Example 13-14 is smaller than that in Example 2, and the surface hardness is greater than that in Example 2. The cathode current efficiency of the cyanide-free electrolyte prepared in Example 15 is slightly lower than that in Example 2, and the particle size of the hard gold electroformed by the cyanide-free electrolyte prepared in Example 15 is slightly larger than that in Example 2, and the brightness is lower than that in Example 2, which shows that increasing the amount of anhydrous sodium sulfite added can improve the cathode current efficiency during electroforming, but if the amount added is too large, it will affect the brightness of the gold product finally obtained.

[0056] The difference between Examples 16-17 and Example 2 is that the pH regulator is different. It can be seen from Tables 1 and 2 that the cathode current efficiency of the cyanide-free electrolyte prepared in Examples 16-17 is lower than that in Example 2. The particle size of the hard gold electroformed by the cyanide-free electrolyte prepared in Examples 16-17 is larger than that in Example 2, and the hardness is lower than that in Example 2. Experimental data show that compared with the disodium hydrogen phosphate-sodium dihydrogen phosphate system and the acetic acid-sodium acetate system, the citric acid-disodium hydrogen phosphate system can further improve the stability of the electrolyte, refine the grain size of the cast gold layer, enhance the density of the cast gold layer, and improve the surface hardness of the cast gold layer.

[0057] The cathode current efficiency of the cyanide-free electrolyte prepared in Comparative Example 1 is lower than that of Example 2. The particle size of the hard gold electroformed by the cyanide-free electrolyte prepared in Comparative Example 1 is larger than that of Example 2, the hardness is lower than that of Example 2, and the brightness and uniformity are lower than those of Example 2. There is blistering after burning. Experimental data show that the further addition of a complexing agent in the present application can significantly improve the stability of the electrolyte, refine the grain size of the cast gold layer, enhance the density of the cast gold layer, improve the surface hardness of the cast gold layer, and enhance the product quality of the hard gold.

[0058] The cathode current efficiency of the cyanide-free electrolyte prepared in Comparative Example 2-3 is lower than that in Example 2. The particle size of the hard gold electroformed by the cyanide-free electrolyte prepared in Comparative Example 2-3 is larger than that in Example 2, the hardness is lower than that in Example 2, and the brightness and uniformity are lower than those in Example 2. After being burned, there is blistering. The experimental data show that different types of complexing agents will affect the stability of the cyanide-free electrolyte, thereby affecting the product quality of the gold products finally obtained.

[0059] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A cyanide-free electrolyte, characterized in that: The cyanide-free electrolyte contains sodium gold sulfite, ethylenediamine, organic phosphonic acid, a ligand, a pH buffer and anhydrous sodium sulfite, wherein the ligand is 3-mercaptopropionic acid or mercaptosuccinic acid.

2. A cyanide-free electrolyte according to claim 1, characterized in that: The complexing agent is mercaptosuccinic acid.

3. A cyanide-free electrolyte according to claim 2, characterized in that: The content of sodium gold sulfite in the cyanide-free electrolyte (in terms of gold) is 0.5-4 g / L, the molar ratio of ethylenediamine to gold is (3-15):1, the content of organic phosphine salt is 3-4 mL / L, the content of mercaptosuccinic acid is 3.375-16.875 g / L, the content of pH buffer is 10-50 g / L, and the content of anhydrous sodium sulfite is 5-33 g / L.

4. A cyanide-free electrolyte according to claim 3, characterized in that: The content of sodium gold sulfite (in terms of gold) in the cyanide-free electrolyte is 1-4 g / L.

5. A cyanide-free electrolyte according to claim 3, characterized in that: The molar ratio of ethylenediamine to gold in the cyanide-free electrolyte is (6-10):

1.

6. A cyanide-free electrolyte according to claim 3, characterized in that: The content of mercaptosuccinic acid in the cyanide-free electrolyte is 6.750-13.500 g / L.

7. A cyanide-free electrolyte according to claim 3, characterized in that: The content of anhydrous sodium sulfite in the cyanide-free electrolyte is 13-23 g / L.

8. A cyanide-free electrolyte according to claim 1, characterized in that: The pH buffer is a citric acid-disodium hydrogen phosphate system.

9. A method for preparing a cyanide-free electrolyte according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Preparation of sodium gold sulfite Dissolving the gold flakes in aqua regia at a temperature of 70-80°C and concentrating the solution by evaporation to one sixth of the original volume to obtain gold trichloride, then diluting the gold trichloride with water, adding ammonia water thereto and stirring the solution until a precipitate is formed to obtain gold fulminate, then mixing the gold fulminate with anhydrous sodium sulfite solution at a temperature of 40-60°C until the gold fulminate is completely dissolved, and then cooling to obtain sodium gold sulfite; S2. Preparation of cyanide-free electrolyte The gold sodium sulfite, ethylenediamine, organic phosphine salt, complexing agent, pH buffer and anhydrous sodium sulfite prepared in step S1 are added into water and mixed evenly, and the pH value of the system is adjusted to 8-9 to obtain a cyanide-free electrolyte.

10. Hard gold obtained by electroforming with a cyanide-free electrolyte prepared by the preparation method according to claim 9.